Guillain–Barre Syndrome following SARS-COVID-19 Infection: A Case Report from India - Abhishek Singhai; Akshit Budhiraja (Case Reports in Infectious Diseases)
Severe acute respiratory syndrome coronavirus 2 (SARS-COVID-19) is a novel coronavirus that started in Wuhan City in China in December 2019. It can cause acute respiratory infection. Guillain–Barre syndrome (GBS) is an autoimmune disease characterized by rapidly progressing ascending paralysis that is triggered by an infection or immune stimulation which produces an abnormal immune response that targets peripheral nerves. In most cases, it is preceded by a bacterial or viral infection. This is a case of a 36-year-old male patient from India who developed progressive acute flaccid paralysis after SARS-COVID-19 infection. Clinical examination and lab studies lead to the diagnosis of GBS. The patient was treated with intravenous immunoglobulins and supportive treatment. Following treatment, there was a substantial improvement in weakness as reported by the patient and was confirmed by clinical evaluation. This is an uncommon manifestation of SARS-COVID-19 infection and suggests the presence of an immune-mediated process leading to damage of the nervous system.